Addressing gender inequality: Stumbling blocks and roads ahead. (August 2018) - Morgenroth, Thekla; Ryan, Michelle K.
Despite many positive changes in terms of gender equality in recent decades, women remain underrepresented in positions of power and prestige, and continue to shoulder disproportionate amounts of unpaid domestic labor. This special issue brings together an examination of the different ways in which gender inequality can be addressed, the efficacy of such approaches, and the consequences these approaches can have. In this introduction to the special issue, we discuss the focus of past and present gender research and outline issues which have received less attention. We further give an overview of the papers in this special issue, which focus on a diverse range of ways in which gender inequality can be addressed, such as collective action, workplace diversity initiatives and parental leave policies, gender-fair language, and government policies. Taken together, these papers illustrate (a) the importance of ensuring that initiatives are evidence-based, (b) the ways in which we can maximize the effectiveness of interventions, and (c) the need to understand when these initiatives may inadvertently backfire.